Phylogenetic relationship of genus Staurois (Anura Ranidae) via partial 16s ribosomal subunit gene in Sarawak - Nur Athirah, Binti Amirrudin (Universiti Malaysia Sarawak, UNIMAS, 2013)
The partial 16S ribosomal mitochondrial DNA gene was used to infer the phylogenetic relationship of selected species of genus Staurois and elucidated the extent of genetic variation within the genus Staurois. The three from six species that were sequenced and used in phylogenetic analysis are Staurois guttatus, S. latopalmatus, and S. tuberilinguis thar are endemic to Sarawak. Samples are collected from Western part of Sarawak including Kubah National Park, Sebangkoi Recreational Park, dan Batang Ai National Park. A total of 498 bp of 16S subunit gene from 48 samples were analysed using genetic analysis softwares such as Molecular Evolutionary Genetic Analysis 4.1 (MEGA 4.1). The phylogenetic trees were constructed using Neighbour Joining (NJ), Maximum Parsimony (MP), and Maximum Likelihood (ML) analyses. All trees produced similar tree topology showing three major clades that distinguish haplotypes from different species and the sister clades distinguishing haplotypes from Eastern and Western part of Sarawak. It also proven that 16S is the useful genetic marker for the genetic study within the genus level.